Different effects of mechano- and metaboreflex on the central blood pressure waveform - Nakamura, Nobuhiro; Heng, Peng; Hayashi, Naoyuki (Frontiers in Physiology, 2025)
IntroductionThe effect of mechanoreflex on central blood pressure (BP) is unclear, although the influence of metaboreflex has been investigated. A relatively small contribution of the mechanoreflex to the pressor response to exercise has been considered in humans because many studies have failed to isolate the mechanoreflex-mediated pressor response. In a recent study, we successfully isolated a mechanoreflex-mediated pressor response using static passive stretching (SPS) in the forearm. Thus, it is possible to isolate the effect of the mechanoreflex on the central BP using this recently developed method. We investigated the effect of muscle mechanoreflex on central BP and compared the changes in the shape of the central BP waveform during mechanoreflex and metaboreflex.MethodsWe measured 12 healthy males (age, 26 ± 2 years; height, 171.1 ± 5.2 cm; body mass, 63.3 ± 10.3 kg; body fat, 16.7% ± 3.9%; means ± standard deviation [SD]) in this study. All participants performed static passive stretching (SPS) of the forearm for 60 s to isolate the muscle mechanoreflex. They also performed 120 s of isometric handgrip (IHG) at 30% maximal voluntary contraction and underwent 180 s of post-exercise ischemia (PEI) to isolate the muscle metaboreflex. The carotid BP (cBP) waveform was obtained from the right common carotid artery as the central BP waveform. We evaluated the first systolic peak (P1) and second systolic peak (P2) from the cBP waveform.ResultsSPS increased cBP with an increase in P1 (p < 0.05), whereas PEI increased cBP with an increase in P2 (p < 0.05). SPS did not alter augmentation pressure (AP) (p > 0.05), whereas PEI increased it (p < 0.05). The relative change from rest (Δ) in P1 during SPS was positively correlated with that in stroke volume (r = 0.68; p < 0.05), and the ΔAP during PEI was positively correlated with that in total peripheral resistance TPR (r = 0.61; p < 0.05).ConclusionThese results suggest different effects of mechano- and metaboreflex on the change in shape of the central BP waveform; mechanoreflex and metaboreflex deform P1 and P2, respectively.